Mathematical Modeling of Marine Oil Spills in the Luanjiakou District, near the Port of Yantai - Daming Li; Xingchen Tang; Yanqing Li; Xiao Wang; Hongqiang Zhang (Discrete Dynamics in Nature and Society)
This paper presents a simulation method for oil spills in a multi-island area. The simulation considers three parts, which consist of (1) the spreading of an oil slick on its edge as well as the diffusion and drift under dynamic actions, (2) the evaporation and spreading thickness of an oil slick in its interior, and (3) the adsorption and emulsification near shorelines and islands. The Euler-Lagrange method is adopted to track the spill location and particles positions on the edge of oil slicks. A mathematical model of marine oil spills is established for the Luanjiakou District of the Port of Yantai. The flow field verification shows that the BIAS of tidal level, flow velocity, and flow direction is below ±10 cm, 0.11 m/s, and ±2°, respectively, and the oil spill verification captures satisfactory results. Hence, the proposed model could reproduce the oil spill process in this region. Then, we simulate oil spills under various operating conditions. It is concluded that the transport of oil slicks is mainly influenced by flood/ebb currents, whereas the wind plays a major role in the drift and thickness of oil slicks. The study provides an important reference to controlling and handling of accidental oil spills.